Proposition 13 - America's second great tax revolt : a forty year struggle for library survival - Guarria, Charles I. (Emerald Publishing Limited, 2018)
In 1978, the citizens of California took the historic step of voting for Proposition 13, thus reducing property taxes by 57%. Already known as a trend setting state, California's tax revolt was no different, as similar tax revisions quickly spread across the United States of America. In California, state and local governments struggled to find a way to manage the loss in revenue. On many occasions budget cuts were the solution. Library budgets were frequently the target of those cuts. 'Proposition 13 - America's Second Great Tax Revolt' details how libraries prioritized, managed and reacted to hardships in this new world, and have done so in California for the last forty years where Proposition 13 is still the law. Library and information science professionals were facing budget cuts that were as high as 65% with little to no guarantee of what future budgets were to be. The actions they took, and the rationale behind those actions, offer significant lessons to be learned by the library community on both an academic and practitioner level. Exploring the intended and unintended consequences of Proposition 13, this book provides an insightful understanding of how to manage a library budget given a difficult funding situation. It examines the thought processes behind government financing and spending priorities, and considers how libraries can organize, and participate in activism to influence decision makers.
Prelims -- Chapter 1 1978-1979: In the beginning -- Chapter 2 1980-1989: Transition and uncertainty -- Chapter 3 1990-1999: In like a lion out like a lamb -- Chapter 4 2000-2010: Good times bad times in California and countrywide -- Chapter 5 2011-2016: Where are we now? -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Library finance -- California; Libraries -- Taxation -- California; Libraries -- California; Language Arts & Disciplines -- Library & Information Science -- General; Library & information sciences